Reward And Punishment On Student's Motivation In Learning English - Muhammad Khairi Ikhsan; Elmiati Elmiati; Herfyna Asty (JUPE : Jurnal Pendidikan Mandala, 2022)
The purpose of this research is to find information about what types of rewards and punishments are used by teachers in classroom activities. This research is qualitative research with descriptive method. The participants in this study were one English teacher at SMK Kesehatan Padang and students who received rewards and punishments from the teacher in the classroom. To collect data, researchers used instruments, namely observation checklists and interviews. Researchers obtained data on how the role of teachers in using the types of reward and punishment in the classroom, as well as conducting interviews with students who received rewards and punishments in the classroom as participants. Based on data analysis, the researchers concluded that English teachers at SMK Kesehatan Padang use reward and punishment during English language learning. Among the 4 types of rewards and 2 types of punishment studied, the English teacher at SMK Kesehatan Padang uses three types of rewards, namely: social rewards, token rewards, material rewards, while two types of punishment are used, namely: presentation punishment, and removal punishment.